A STUDY TO EVALUATE THE EFFECTIVENESS OF PELVIC FLOOR EXERCISE ON UTERINE PROLAPSE AMONG WOMEN IN SELECTED HOSPITAL - R. Deepa,; Dr. Sathiyalatha Sarathi,; Dr. V. Hemavathy, (The Bioscan, 2025)
Introduction: Pelvic floor exercises (PFEs) have emerged as a vital non-surgical approach to managing uterine prolapse among women. This exercise regimen aims to strengthen the pelvic floor muscles, which can both prevent the onset and mitigate the effects of uterine prolapse. Aim of the study: The aim of the study to evaluate the effectiveness of pelvic floor exercise on uterine prolapse among women in selected hospital. Methodology: This study will employ a pre-experimental design, specifically a one-group pre-test and post-test design, to evaluate the effectiveness of pelvic floor exercises on uterine prolapse in women aged 40 years and above in a selected hospital. Participants will be selected based on their willingness to participate and their ability to comply with the exercise regimen. The intervention will consist of a structured pelvic floor exercise program over 12 weeks, with exercises conducted three times per week. Results: The study showed significant improvements after the pelvic floor exercise intervention. Bach’s Scale for pelvic muscle strength increased from 2.5 (SD = 0.8) to 3.8 (SD = 0.7) (t = 5.30, p < 0.001). The Revised Urinary Incontinence Scale reduced from 12.3 (SD = 3.1) to 8.7 (SD = 2.9) (t = 7.45, p < 0.001). The PFDI-20 scores improved from 35.4 (SD = 6.2) to 26.1 (SD = 5.3) (t = 6.82, p < 0.001), indicating enhanced pelvic health and quality of life. Conclusion: The present study concluded that the pelvic floor exercise intervention proved to be highly effective in improving pelvic muscle strength, reducing urinary incontinence, and enhancing overall quality of life for women with uterine prolapse.